2017
DOI: 10.1097/md.0000000000007613
|View full text |Cite
|
Sign up to set email alerts
|

18F-fluoro-deoxy-glucose positron emission tomography combined with computed tomography can reliably rule-out infection and cancer in patients with anti-neutrophil cytoplasmic antibody-associated vasculitis suspected of disease relapse

Abstract: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a group of autoimmune diseases characterized by systemic inflammation in small- to medium-sized blood vessels. Although immunosuppressive therapy has greatly improved the prognosis for these patients, there are still significant comorbidities, such as cancer and infection, associated with AAV. These comorbidities are often indistinguishable from an underlying AAV disease relapse, and create a clinical conundrum, as these conditions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
(30 reference statements)
0
2
0
3
Order By: Relevance
“…At the time of FDG administration, all patients had fasted for at least 6 hours. 18 F-FDG-PET/CT image acquisition commenced 60±5 minutes after the administration of a weight adjusted dose of 4 MBq/kg FDG (200-400MBq) [13].…”
Section: Imaging Protocolmentioning
confidence: 99%
“…At the time of FDG administration, all patients had fasted for at least 6 hours. 18 F-FDG-PET/CT image acquisition commenced 60±5 minutes after the administration of a weight adjusted dose of 4 MBq/kg FDG (200-400MBq) [13].…”
Section: Imaging Protocolmentioning
confidence: 99%
“…İmmünsüpresif tedavi ile prognoz iyileşme göstermiştir, fakat tedavi ile ilişkili komorbiditeler endişe olarak kalmaya devam etmektedir (6). Granülomatöz polianjiit tanılı hastanın izleminde hastalığın doğasına veya tedaviye bağlı olarak enfeksiyon riski artmaktadır (7).…”
Section: Discussionunclassified
“…Bizim olgumuzda da başlangıçtan ex olana kadar akut faz yanıtları yüksek saptanmış olup, klinik olarak bunların ayrımının yapılabilmesi zorlaşmaktadır. Hastalık aktivasyonu, enfeksiyon ve malignite ayrımı için pozitron emisyon tomografisi (PET) ve BT birleşimi ile ayrım yapabileceğini gösteren çalışmalar olmakla beraber klinik uygulaması çok kolay değildir (7).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Same group reported two cases of asymptomatic aortic arch involvement in ANCAassociated vasculitis diagnosed with FDG-PET/CT (73). Finally, a small retrospective study from Frary et al found FDG-PET/CT to have high accuracy and predictive values for differentiating disease relapse of ANCA-associated vasculitides from infection and malignancies, two important differential diagnoses with often indistinguishable symptoms and signs (74).…”
Section: Small Vessel Vasculitismentioning
confidence: 99%